Implementasi Metode TAM Untuk Menganlisa Penerimaan Teknologi Aplikasi Peduli Lindungi - Sefrika, S (STIKOM Tunas Bangsa Pematangsiantar, 2021)
To prevent the spread of the COVID-19 virus, the government has issued a caring and protective application that can be accessed on the user's mobile device. The caring protection application aims to protect and trace contact history and provide notifications if the user is in the red zone, namely an area infected with covid19. This study aims to determine whether the application of care to protect is used and well received by the community by using the Technology Acceptance Model (TAM) method. TAM is an information systems theory that creates a model that is used to analyze how users are willing to accept and use a technology. The results of the study indicate that the interest in using the Care Protect application has a significant effect on the actual use of the application based on research that has been carried out on respondents.